The relationships between hours of television viewing, parenting styles and children aggression in Sabah - Aminuddin Ibrahim Lastar (2011)
The objective of this study was to examine the relationship between excessive hours of television viewing and aggressive behaviors amongst children in Sabah. Different role of parenting styles adopted by parents that may contribute to the occurrences of aggressive behaviors amongst their children were also been examined for moderator. The study was conducted in various rural and urban areas of Sabah, involving 626 samples; male (N= 367) and female (N=259) children. A self-developed questionnaire based on the adaptation from Child Behavior Check List (CBCL) by Achenbach (1991), Childhood TV Violence Measures (CTWM) by Huesmann and Eron (1986) and Parental Authority Questionnaire (PAQ) by Buri (1991) was used in this study. Data gathered from the survey was analyzed by using Pearson Product-Moment Correlation Coefficient, T-Test, and Hierarchical Multiple Regression. The findings showed that, children in Sabah spend 3.3 hours a day watching television programs has a Significant positive correlations (r=.12, p <0.05) with infringement. It is also found that the occurrence of infringement is momentous in the rural area compare to urban with a significant in score for urban (M=14.16, 50=2.82), and rural area [M=15.24, SD=3.17;t(624) = -4.46, p<0.05]. Parenting styles that play a very important role in this occurrence was tested for the predictor. Authoritative parenting style was found has a significant moderation effect [F (3,620)=4.09,P <0.05)]. It has reduced the manifestation of aggressiveness in the children's behaviors. Consequently, authoritative parenting style is an essential element in bringing up children in order to educate them from acting aggressive due to the influence of the television programs watched.